The knowledge, attitude, and practice toward fall prevention of parturients in the obstetric inpatient wards: a comparative cross-sectional study between nurses and parturients - Jing Wen; Jing Wen; Jiao Wen; Jiao Wen; Wenjuan Jing; Wenjuan Jing; Hongmei He; Hongmei He; Jianhua Ren; Jianhua Ren (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to compare the knowledge, attitudes, and practices of parturients and nurses regarding fall prevention among parturients, with the goal of understanding the cognitive factors contributing to post-delivery fall.MethodsA cross-sectional survey was conducted among obstetric nurses and women in obstetric ward within 2 days after vaginal delivery. The survey instrument included a self-design questionnaire comprising a demographic information sheet and a KAP questionnaire, which demonstrated acceptable reliability and validity.ResultsA total of 705 nurses and 1,220 parturients completed the survey. Over half of both nurses and parturients exhibited reasonably good knowledge, positive attitudes and appropriate practices related to fall prevention. Significant associations were identified between the education level of parturients and their knowledge and attitudes. Nurses scored lower in the attitude dimension compared to parturients (4.32 ± 1.01 vs. 4.84 ± 0.36, P < 0.001), whereas nurses scored higher than parturients in the practice dimension (3.76 ± 0.44 vs. 3.57 ± 0.48, P < 0.001).ConclusionNurses should focus on enhancing the fall practices of parturients by emphasizing key points for fall prevention and providing guidance in situations of improper behaviors (e.g., unaccompanied activities). Further education programs for nurses should prioritize increasing their confidence and proficiency in fall prevention.